2020
DOI: 10.17826/cumj.694074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorhexidine gluconate solution on healing process in care of episiotomy wound

Abstract: Öz Purpose: Determination of the effect of chlorhexidine gluconate (CG) solution (containing 70% alcohol) on the process of episiotomy wound healing. Materials and Methods: This is a semi-experimentally designed study with pre-test post-test control group. In the research, after the episiotomy intervention 45 puerperal, those were treated with routine hospital care formed the control group, the other 45 puerperal who were treated with Serum Physiological (SP) solution formed the 1st group and the remaining 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…23 Çobanoğlu and Şendir evaluated the effect of chlorhexidine gluconate on healing of episiotomy and noted that chlorhexidine gluconate was an effective care product and could be used to support wound healing. 24 Although there have been many studies proving the effectiveness of chlorhexidine, some studies have shown that povidone iodine is more effective than chlorhexidine. [25][26][27] McLure and Gordon examined effects of povidone iodine and chlorhexidine on 33 strains of MRSA and found that while chlorhexidine was effective in 3 strains of MRSA, povidone iodine was effective in 33 strains.…”
Section: Discussionmentioning
confidence: 99%
“…23 Çobanoğlu and Şendir evaluated the effect of chlorhexidine gluconate on healing of episiotomy and noted that chlorhexidine gluconate was an effective care product and could be used to support wound healing. 24 Although there have been many studies proving the effectiveness of chlorhexidine, some studies have shown that povidone iodine is more effective than chlorhexidine. [25][26][27] McLure and Gordon examined effects of povidone iodine and chlorhexidine on 33 strains of MRSA and found that while chlorhexidine was effective in 3 strains of MRSA, povidone iodine was effective in 33 strains.…”
Section: Discussionmentioning
confidence: 99%